KHITBAH SANTRI JAMA’AH TABLIGH DI PONDOK PESANTREN AL-FATAH TEMBORO KABUPATEN MAGETAN - Khotami, Dewi Afifatul; Samsukadi, Mochamad; Makmun, Moh (Fakultas Agama Islam UNISMA, 2023)
This study starts from the framework of thinking that the sermon carried out by the Tablighi Jama'ah santri at the Al-Fatah Islamic Boarding School Temboro, Magetan Regency, is a form of the sermon process that applies legal rules and regulations such as the prevailing Islamic law or fiqh munakahat. For this reason, at the beginning of starting the intention to preach from the male students, sowan came to meet the Kyai, Ahlu Shuro' (a legal expert in discussing a problem with the muftis to produce a fatwa by means of ijtihad). After that proceed to the nadzor process (seeing potential partners) with the aim of not causing regret between the two parties in the future when the marriage contract occurs. Besides that, the santri sermon at Pondok Al-Fatah Temboro not only runs perfectly, there are also problems with cancellation or termination of the sermon either by one party or both parties directly canceling it due to the factors that influence it. The purpose of this study is to find out how the preaching of the Tablighi Jama'ah santri at the Al-Fatah Islamic Boarding School Temboro and to find out the form of relevance of the sermon in Islamic law. This study uses a qualitative approach or field research with the miles and huberman method.